Enhancing Religious Values ​​and Moral Character in Early Childhood Through Growth Mindset-Based Islamic Storytelling Strategies: A Mixed-Methods Study - Sakila Sapna; Durrotunnisa; Fitriana; Nurhayati (Universitas Al-Hikmah Indonesia, 2026)
This research is motivated by the importance of developing religious values and moral behavior in early childhood as a foundation for character formation. One strategy that can be used to instill these values is Islamic stories combined with a growth mindset approach. This study aims to determine the improvement of religious values and moral character in early childhood through a growth mindset-based Islamic story strategy. The study used a mixed methods approach with an explanatory sequential design. The research subjects were 10 children aged 5–6 years. Quantitative data were obtained through observations using religious values and moral character assessment sheets given before (pretest) and after treatment (posttest), while qualitative data were obtained through observations during the learning process and documentation of children's activities. Quantitative data analysis was carried out descriptively and inferentially using the Wilcoxon Signed Rank Test method, while qualitative data were analyzed descriptively to clarify the results of the quantitative data analysis. The study showed that the average value of religion and moral character of children increased from 13 in the initial trial to 21.9 in the final trial. The results of the Wilcoxon Test showed that all children experienced an increase in scores after treatment. Qualitative findings indicate that children are more enthusiastic about participating in learning activities, are able to identify good behaviors through Islamic stories, are active in coloring and discussion activities, and are able to practice religious values and morals through role-playing activities. Combining the results of quantitative and qualitative research indicates that a growth mindset-based Islamic story strategy is quite effective in improving religious values and moral attitudes in early childhood. This is achieved through learning experiences that are meaningful, enjoyable, and developmentally appropriate.